2021
DOI: 10.1186/s12902-021-00686-w
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of antidiabetic medicines in Portugal: results of a temporal data analysis of a thirteen‐year study (2005–2017)

Abstract: Background Studies of drug utilization in patients with diabetes, a chronic disease that can be treated with a wide range of available medicines, have attracted substantial social and clinical interest. Objective To characterize antidiabetic medicine consumption between 2005 and 2017, to evaluate the trends of these medicines in mainland Portugal, and to compare district consumption. An additional objective was to perform a statistical analysis on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
(6 reference statements)
1
6
0
Order By: Relevance
“…Therefore, the possible influence such as the regional difference in the market share was ignored. The trend of prescription of antidiabetic medications in other countries are similar to that of Japan [13,14]. Therefore, our observation would be reproducible in many if not all countries all over the world.…”
Section: Discussionsupporting
confidence: 72%
“…Therefore, the possible influence such as the regional difference in the market share was ignored. The trend of prescription of antidiabetic medications in other countries are similar to that of Japan [13,14]. Therefore, our observation would be reproducible in many if not all countries all over the world.…”
Section: Discussionsupporting
confidence: 72%
“…DPP4Is have neutral effects on weight and cardiovascular and renal problems with moderate effect on blood glucose control, and their use is preferred if the main goal is to improve glucose control without hypoglycemia in the case of elder, frail people [ 3 , 4 ]. The emerging use of DPP4Is, SGLT2Is and GLP1As use has also been observed in other countries’ utilization data, such as Denmark or Portugal [ 9 , 19 ].…”
Section: Discussionmentioning
confidence: 73%
“…Previously published data on the utilization of antidiabetic medicines in Italy and Portugal revealed substantial regional differences [ 8 , 9 ]. Regional differences in medication use can be associated with several factors.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported the prescription trends of SGLT-2is, [6][7][8][9][10][11][12] revealing that the prescription of SGLT-2is has increased over time. Engler et al 8 reported that prescription trends changed after 2015, when the EMPA-REG OUTCOME study was published.…”
Section: What Is Known and Objectivementioning
confidence: 99%